La Segmentación De Mercado Y La Satisfacción Del Cliente En Los Negocios Comerciales De La Bahía De Guayaquil - Rosa Espinoza Toalombo; Jenniffer Alchundia; Xavier Layana; Xiomara Zuñiga; Diego Tapia; Wilmer Espinoza (European Scientific Journal, ESJ, 2018)
Currently, majority of people who make up the society have a lot of different needs that the market must be willing to meet. The application of the segmentation strategy allows the offering of a commercial mix for the different types of consumers, giving the opportunity to customize and structure a unique combination of elements such as product, price, place, and promotion. This value proposition is potentially superior to that of competition. As a result, this is why it is imperative to study the segmentation of the market and the impact that this gives to the satisfaction of customers who like the goods and services offered in the Bay of Guayaquil. It, however, focuses on contributing to the improvement of the structure and positioning of these markets. The methodology used is empirical-positivist because it generates a new knowledge. The field is in relation to the sample that was surveyed. This study is exploratory because they intend to give us an overview regarding a reality. Finally, the study is descriptive because it details the results of the study. The adaptation of market segmentation is a feasible strategy to meet the needs of consumers and mitigate the risks that the markets present. As a result, it is advisable to divide it by groups in order to differentiate consumers and respond more safely to their preferential needs.